Comparing Volumetric Dimensional Stability and Accuracy of Newly Formulated Polyvinyl Siloxanether, Polyvinyl Siloxane and Polyether Impression Materials Using Micro-Computed Tomography - (:unkn) unknown (MARMARA UNIV, INST HEALTH SCIENCES, 2019)
Objective: The purpose of this study was to compare volumetric dimensional accuracy and stability of polyvinylsiloxane, polyether and new formulated polyvinylsiloxanether impression materials by using micro-computed tomography. Methods: A total of 42 impressions were made of stainless steel metal dyes. Polyvinylsiloxane, Polyether and Polyvinylsiloxanether impressions were taken for volumetric dimensional accuracy and stability to measure by Micro-computed tomography (mu CT). Impression materials were measured for dimensional stability after the impression was taken, 24 hours later and 144 hours later. For dimensional accuracy 21 impressions and 21 stone models of these impressions were measured. One-way analysis of variance was be used to test for statistically significant difference within groups and Tukey's test was be used to test for across groups with a significance value of p < 0.05. Results: After polymerization, although polyether impression negative was shown to have the highest volumetric expansion, the highest shrinkage was observed in the same group after pouring to dental stone. Stone model of the polyether was observed as the most accurate value of volume in comparison to the master model. The lowest volumetric dimensional change was observed in polyvinylsiloxanether at day 1 (-0.004 +/- 0.001%) and the highest change was observed in polyether at day 7 (-0.052 +/- 0.004%). Conclusion: From the standpoint of volumetric accuracy and stability, all three elastomeric impressions are acceptable and mu CT is a useful tool for assesments of volumetric dimensional changes.
Keywords: Volumetric dimensional accuracy and stability; Micro CT; polyvinylsiloxanether; 3-DIMENSIONAL MEASUREMENT; MICROCOMPUTED TOMOGRAPHY; DETAIL REPRODUCTION; LASER SCANNER; CASTS; SILICONE; SHRINKAGE; MONOPHASE; SYSTEM